Investigations of uncertainty of acoustical measuring instruments applied to noise control - Wszołek, G.; Engel, Z. (Archives of Acoustics, 2004)
In view of regulations harmonised with the European Union legislation, being presently introduced in Poland, it is required that the presentation of the measured sound level values is accompanied by the uncertainty study. It is especially important in cases concerning an acoustical environment of human life and work. The uncertainty study comprises, among others, accuracy of the measuring instrument itself and its calibration prior to the measurements as well as uncertainty of the measuring method and the way of the test performance. The first element of this estimate is uncertainty of testing measuring microphones and sound level meters in order to verify whether they conform to the requirements being set for the newly manufactured instruments at the stage when they are subjects to the type approving procedure.